Comparative Evaluation of Date Palm Types (Phoenix dactylifera L.) under the Conditions of the Northern State, Sudan - Idris , Tagelsir I.M.; Mahdi, Elfatih M.; Khidir , Omaima S.A. (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was accomplished to assess the comparative performance of the dry, semi-dry and soft date palm types under the conditions of the Northern State, Sudan. Four date representative cultivars, grown in Elghaba Agricultural Scheme, were compared;.their age ranged between 30 and 34 years. The cultivars were Barakawi and Gondaila (dry), Wadkhteeb (semi-dry) and Madina (soft). Data recorded for vegetative growth parameters were stem circumference, leaf number and length, number of pinnae/leaf, length of pinnae, number of thorns/leaf and width of leaf base. Data were also collected for number of bunches, bunch weight and yield/palm. The results indicated significant differences between the four cultivars. Wadkhteeb excelled the other cultivars in number of leaves, bunch weight and yield/palm, without being affected by the phenomenon of alternate bearing. The superiority of Wadkhteeb in yield is indicative of the suitability of the semi-dry cultivars to the conditions of the Northern State.